Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
(a) The solution to the system of equation is, x = (d + b)/(ad - cb) and y = (-a - c)/(ad - cb).
(b) The condition at which the solution exists is, ad - cb ≠ 0.
Solving the system of equation with Cramer's rule
ax + by = 1
cx + dy = -1
D = [a b]
[c d]
D = ad - cb
Dx = [1 b]
[-1 d]
Dx = d + b
Dy = [a 1]
[c - 1]
Dy = -a - c
x = Dx/D
x = (d + b)/(ad - cb)
y = Dy/D
y = (-a - c)/(ad - cb)
Cramer's rule applies to the case where the coefficient determinant is nonzero.
Thus, D ≠ 0 (ad - cb ≠ 0).
Learn more about Cramer's rule here: https://brainly.com/question/10445102
#SPJ1
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.
my father is 4 times old as me. after 5 years my father will be 3 times old how old is my father now